Data from: Wintering sea duck distribution along the Atlantic coast of the United States - Silverman, Emily D.; Saalfeld, David T.; Leirness, Jeffery B.; Koneff, Mark D. (Zenodo, 2013)
Although monitoring data for sea ducks (Tribe Mergini) are limited, current evidence suggests that four of the most common species wintering along the eastern coast of the United States—long-tailed duck Clangula hyemalis, white-winged scoter Melanitta fusca, surf scoter Melanitta perspicillata, and black scoter Melanitta americana—may be declining, while the status of American common eider Somateria mollissima dresseri is uncertain. The apparent negative trends, combined with the fact that sea duck life histories are among the most poorly documented of North American waterfowl, have led to concerns for these species and questions about the impacts of human activities, such as hunting, as well as catastrophic events and environmental change. During winter, thousands of sea ducks are found along the U.S. Atlantic coast, where they may be affected by proposed wind-power development, changes to marine traffic, aquaculture practices, sand mining, and other coastal development. Possible impacts are difficult to quantify because traditional winter waterfowl surveys do not cover many of the marine habitats used by sea ducks. Thus, the U.S. Fish and Wildlife Service conducted an experimental survey of sea ducks from 2008 to 2011 to characterize their winter distributions along the U.S. Atlantic coast. Each year, data were collected on 11 species of sea ducks on >200 transects, stretching from Maine to Florida. In this paper, we describe distribution of common eider, long-tailed duck, white-winged scoter, surf scoter, and black scoter. Densities of the two species with the most northerly distribution, white-winged scoter and common eider, were highest near Cape Cod and Nantucket. Long-tailed duck was most abundant around Cape Cod, Nantucket Shoals, and in Chesapeake Bay. Surf scoter also concentrated within Chesapeake Bay; however, they were additionally found in high densities in Delaware Bay, and along the Maryland–Delaware outer coast. Black scoter, the most widely distributed species, occurred at high densities ...